Pengaruh Firm Growth dan Total Asset Turnover Terhadap Kinerja Keuangan - Savitri, Rachmalia Jeany; Purwohedi, Unggul; Zakaria, Adam (LPPM Universitas Negeri Jakarta, 2023)
This research aims to determine the effect of sales growth, asset growth, and total asset turnover on financial performance. The research uses secondary data in the form of financial statements that can be seen on the Indonesia Stock Exchange (IDX) website. The population in this research is manufacturing companies listed on the IDX in 2021 - 2022. This research used purposive sampling techniques to produce a sample of 96 companies. The method used in this research is quantitative method. This research used descriptive statistical analysis techniques and panel data regression analysis. The research was processed using Eviews 12 software. The results of this research show that sales growth negatively affects financial performance. Asset growth has a positive effect on financial performance. Meanwhile, total asset turnover does not affect financial performance.